Joint costs and their impact on the profitability of a milling company in the Lambayeque region - Burga Becerra, Ariana Stephany; Hernández Díaz2, Adrián Eduardo; Obregon Vara, Flor Elizabeth; Pintado Castillo, Cesar Agusto (LACCEI, 2025)
This study analyses the impact of joint cost allocation on the profitability of a milling company in the Lambayeque region in 2024. The main issue is the imprecision of cost allocation within joint production processes, which affects the determination of accurate prices and the profitability. Based on methods such as net realisable value and market value at the split-off point, a joint costing proposal was designed to improve cost distribution between products derived from the rice milling process. The quantitative, descriptive-correlational and non-experimental research design primarily employed document analysis of accounting records aligned with the rice milling production process. The results demonstrate that implementing a joint costing system optimises profitability, improves cost control and provides more accurate management information. It is concluded that joint costing has a positive impact on the profitability of the milling company studied, enabling more accurate and competitive decision-making